RISK MANAGEMENT IN THE BANKING SECTOR OF MAURITIUS - Sunecher, Yuvraj; Dookhy, Nitisha Saiswari (Bank Indonesia, 2025)
This study examines the factors contributing to fraud in banks, which has gained mainstream attention recently from high-value fraud events. It revolves around themes of different factors contributing to this issue, especially fraud within the banks that have gained mainstream attention in recent major value fraud events. The factors mentioned in this study are pressure, opportunity, and rationalisation, which are elements of the fraud triangle theory. For this study extension, internal management factors have also been included, including internal audit activities, top management support, and risk management. Data was collected from 160 bank officers from the top 10 banks in Mauritius, and the results were analysed. The main outcome suggests that bank officers are not tempted or willing to commit fraud if their remunerations are satisfactory, and internal management factors play an important role in detecting and preventing banking embezzlement. This study provides insight and awareness of internal banking threats and how to enhance the banking system.